Desain dan Uji Coba Buku Ajar berbasis Science, Technology, Engineering and Mathematics pada Materi Asam Basa - Azura Azura; Zona Octarya (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
This research was instigated by the low of learning media integrating with the other sciences. It aimed at designing a print mediaintegrating chemistry science with other sciences on Chemistry subject, then it would be tested its validity by the experts of media and material and its practicality to Chemistry subject teachers, and it would be tested to the students. In this research, Chemistry instructional media in the form of Testing Science, Technology, Engineering, and Mathematics (STEM) basedtextbook was designed by using Microsoft Word software. The final product result was a valid instructional media. It was a Research and Development (R&D) with Borg and Gall modification model, and it was administered at State Senior High School Plus Riau Province. Techniques of collecting the data were interview, questionnaire, and documentation. STEM based textbook that was designed gained 96.1% validity percentage, and it meant that the textbook was stated very valid. The percentage of textbook practicality was 90.45%, it was stated very practical and the textbook got good student response that its percentage was 89.8%. Based on these findings, it could be concluded that Chemistry instructional media in the form of STEM based textbook on Acid Base lesson had been valid, practical, able to get good student responses.